2008
DOI: 10.1158/1055-9965.epi-07-0678
|View full text |Cite
|
Sign up to set email alerts
|

Full-term Pregnancy Induces a Specific Genomic Signature in the Human Breast

Abstract: Breast cancer risk has traditionally been linked to nulliparity or late first full-term pregnancy, whereas young age at first childbirth, multiparity, and breastfeeding are associated with a reduced risk. Early pregnancy confers protection by inducing breast differentiation, which imprints a specific and permanent genomic signature in experimental rodent models. For testing whether the same phenomenon was detectable in the atrophic breast of postmenopausal parous women, we designed a case-control study for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
93
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 77 publications
9
93
0
Order By: Relevance
“…This work confirmed that pregnancy had a protective effect that was evident from the early teen years and persisted until the middle twenties [1]. Other studies have reported that additional pregnancies and breastfeeding confer greater protection to young women, including a statistically significantly reduced risk of breast cancer OPEN ACCESS in women with deleterious BRCA1 mutations who breast-fed for a cumulative total of more than one year [3,4]. Our studies, designed to unravel what specific changes occurred in the breast during pregnancy that confer a lifetime protection from developing cancer, led us to the discovery that endogenous endocrinological or environmental influences affecting breast development before the first full term pregnancy were important modulators of the susceptibility of the breast to undergo neoplastic transformation.…”
Section: Introductionsupporting
confidence: 71%
“…This work confirmed that pregnancy had a protective effect that was evident from the early teen years and persisted until the middle twenties [1]. Other studies have reported that additional pregnancies and breastfeeding confer greater protection to young women, including a statistically significantly reduced risk of breast cancer OPEN ACCESS in women with deleterious BRCA1 mutations who breast-fed for a cumulative total of more than one year [3,4]. Our studies, designed to unravel what specific changes occurred in the breast during pregnancy that confer a lifetime protection from developing cancer, led us to the discovery that endogenous endocrinological or environmental influences affecting breast development before the first full term pregnancy were important modulators of the susceptibility of the breast to undergo neoplastic transformation.…”
Section: Introductionsupporting
confidence: 71%
“…In perhaps the only previous study to address the effect of parity on gene expression profiles in the normal breast, Russo and coworkers applied cDNA microarrays to ethanolfixed tissue obtained from postmenopausal women (34)(35)(36). In this discovery effort, a large number of genes were found to be differentially expressed between parous and nulliparous women, including a number of immune-related genes that were upregulated in the parous group.…”
Section: Discussionmentioning
confidence: 99%
“…Both pregnancy and breastfeeding have long-term protective effects against breast cancer because of the increased differentiation of breast tissue under the effect of female hormonesmainly progesterone. [48][49][50][51] Increased age of marriage leads to a lack of differentiation in the breast tissue making it more susceptible to harmful effects of nonestrogenic mutagens as well as genotoxic effects of estrogen, which has been known to cause ER2 breast cancers as well. 52,53 Moreover, being married and having children might also reduce the level of circulating hormones or increase the levels of sex hormone-binding globulin.…”
Section: Discussionmentioning
confidence: 99%